User Experience of a Mobile App in a City Tour Game for International Doctoral Students - Margarida M. Marques; Lúcia Pombo (MDPI AG, 2023)
Mobile augmented reality games (MARGs) offer exciting possibilities for enriching outdoor learning and enhancing tourism experiences. However, there is a notable gap in understanding the perspectives of doctoral students on these innovative approaches. This paper presents the results of a case study conducted during the 2023 EERA Summer School in Portugal, where PhD students in Education, from universities all around the globe, engaged in a MARG for sustainable development education. Seventy-three students embarked on a walking city tour, whilst playing an interdisciplinary game supported by the EduCITY Smart Learning City Environment. It comprises a web platform, an app, location games, and game creation training. Students experienced the EduCITY app, which guided them through a designated city path encompassing tourist sites, while promoting diverse learning opportunities. At the end, students provided feedback through a short and anonymous evaluation questionnaire, incorporating the user experience questionnaire and one open-ended question for improvement suggestions. This study revealed valuable insights into the doctoral students' perspectives on the EduCITY app's user experience, highlighting the strengths of "Attractiveness", "Stimulation", and "Novelty". However, it also identified areas for improvement, particularly in "Dependability" and "Efficiency". The analysis of the open-ended responses suggested that "Attractiveness" and "Perspicuity", while not immediate priorities, should be considered in refinement phases as well. As more and more students recognize the importance of MARGs in education, there is a growing need for research in this field, aligning with the 2030 Agenda for Sustainable Development, Goal 4.